2006
DOI: 10.1128/jcm.44.4.1502-1508.2006
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Amplification and Molecular Typing of the Obligate Intracellular Pathogen Mycobacterium leprae Isolated from Tissues of Unknown Origins

Abstract: Molecular diagnostic and epidemiology studies require appreciable amounts of high-quality DNA. Molecular epidemiologic methods have not been routinely applied to the obligate intracellular organism Mycobacterium leprae because of the difficulty of obtaining a genomic DNA template from clinical material. Accordingly, we have developed a method based on isothermic multiple-displacement amplification to allow access to a high-quality DNA template. In the study described in this report, we evaluated the usefulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Therefore, using MDA-amplified bacterial DNA derived from few bacterial cells may help to accomplish bacterial genotyping at reasonable costs and time. This is in accordance with similar studies were it was shown that MDA-amplified DNA derived from few bacterial cells and human biopsy specimens provided a reliable and representative source for multiple molecular typing analysis (Monstein et al, 2005;Groathouse et al, 2006;Ryberg et al, 2008;Tärnberg et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, using MDA-amplified bacterial DNA derived from few bacterial cells may help to accomplish bacterial genotyping at reasonable costs and time. This is in accordance with similar studies were it was shown that MDA-amplified DNA derived from few bacterial cells and human biopsy specimens provided a reliable and representative source for multiple molecular typing analysis (Monstein et al, 2005;Groathouse et al, 2006;Ryberg et al, 2008;Tärnberg et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…By contrast, an automated nucleic extractor combined with multiple displacement amplification (MDA) of bacterial DNA yields DNA of high purity that can be used in multiple downstream applications. In recent years, MDA has been tried out for microbial and total DNA (bacterial and cellular) isolated from human biopsy specimens [20,21,23]. The present study shows the feasibility of using MDA-amplified bacterial DNA as a source in bla SHV, bla LEN and bla OKP genotyping analysis of K. pneumoniae clinical isolates having an ESBL-phenotype.…”
Section: Discussionmentioning
confidence: 85%
“…caves (Gonzalez et al. , 2005), insects (Jeyaprakash and Hoy, 2004), human skin (Groathouse et al. , 2006), corals (Yokouchi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial communities have been analysed in, e.g. caves (Gonzalez et al, 2005), insects (Jeyaprakash and Hoy, 2004), human skin (Groathouse et al, 2006), corals (Yokouchi et al, 2006), subsurface and contaminated soils (Abulencia et al, 2006), marine viral assemblages (Angly et al, 2006) and contaminated groundwater (Wu et al, 2006). Communities that have been subjected to WCGA (Erwin et al, 2005;Kalyuzhnaya et al, 2006;Chen et al, 2008;Neufeld et al, 2008) include those involved in important biogeochemical functions, e.g.…”
Section: Introductionmentioning
confidence: 99%